الطباعة بالحروف المتحرکة فى الشرق الاوسط - د.شعبان خلیفة (المجلة الدولية لعلوم المكتبات والمعلومات)
This quick paper aims at crystalizing the introduction anddevelopment of movable type printing in the Middle East Countries. Itbegins with an overview on the invention of printing and its spread in theMiddle East. The paper concentrates on the printing of Arabic LanguageWorks. The main points of the Subjects run as follows:1. Arabic printing in Europe Since 1514.2. Arabic printing in Istanbul.3. Arabic printing in Egypt.4. Arabic printing in Syria and Lebanon.5. Arabic printing in Iraq.6. Arabic printing in Palestine and Jordan.7. Arabic printing in Arabia.8. Arabic printing in North Africa.9. Arabic printing in India.10.Sample pages illustrating all stages of Arabic printing through1500-1950.